Quality evaluation of functional carabeef cookies incorporated with guar gum (Cyamopsis tetragonoloba) as fat replacer. Issue 3 (26th October 2018) - Goswami, Meena; Sharma, B.D.; Mendiratta, S.K.; Pathak, Vikas
Abstract : Purpose: This study aims to evaluate the quality characteristics of low-fat functional carabeef cookies incorporated with different levels of guar gum. Design/methodology/approach: Meat cookies were incorporated with 0.5, 1.0 and 1.5 per cent guar gum powder to replace 20, 30 and 40 per cent hydrogenated vegetable fat, respectively. The formulation of low-fat carabeef cookies was maintained by addition of water. Findings: There was a significant difference ( p < 0.02) between control and treatments for all physico-chemical properties, except pH and thickness. The cooking yield increased significantly ( p < 0.04) at 1.5 per cent level of guar gum. Moisture, protein and ash percentage increased significantly ( p < 0.02) while there was significant ( p < 0.00) reduction in fat percentage. The diameter and spread ratio of cookies decreased significantly ( p < 0.03) with incorporation of guar gum. The sensory scores were not significantly affected with respect to color and appearance, flavor, texture, crispiness, aftertaste and overall acceptability at 1.5 per cent level. There was no significant difference in hardness and adhesiveness values, as well as color parameters. Research limitations/implications: The experiment can be further carried out to evaluate complete product profile and storage stability of product under different packaging conditions. Originality/value: Fat imparts richness and tenderness, improving flavor and mouth feel to processed meat products, but higher fat consumption may lead to various life style diseases. Reducing fat content with fat replacers in meat cookies without affecting the sensory characteristics may be a significant challenge. Guar gum powder may be an excellent option at 1.5 per cent level to replace 40 per cent of hydrogenated vegetable fat without compromising quality attributes.